Intensifying of Stock Markets (DSE & CSE) in Bangladesh: An Experiment - Huda, Syed Nazmul (Asian Business Review, 2013)
A stock market plays as a strong role in the industrialization and economic development of the country. Among the developing countries, the contribution of the capital market have lately been recognized. This paper assess the Intensifying of Stock Markets (DSE & CSE) in Bangladesh based on Dhaka Stock Exchange (DSE) & Chittagong Stock Exchange (CSE). Information collected from secondary data during 2000-2011 along with identifying the major dominants factors and some problems or lacks of stock market whish is greatly obstacle to intensifying the stock market in Bangladesh.  By using the factor analysis it has been shown that Turn over of capital market largely depends on four indicators i.e. No. of Listed Securities, Initial Public Offering (IPOs), Market Capitalization, Issued Capital in the both stock markets in Bangladesh during the study period. The authors to identify the  some problems or lacks of stock market in Bangladesh which has been face the market crash in recent years and doing experiment to find out the dominants factors to overcome problems as well as develop the stock  market during the study period.
Keywords: Dhaka Stock Exchange; Chittagong Stock Exchange; Keiser Mayer Olkin